2016
DOI: 10.3945/ajcn.115.129478
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of black and white Americans and changes in vitamin D metabolites after varied doses of vitamin D supplementation

Abstract: The relation between free and total 25(OH)D did not vary systematically by race in this multiracial population with pre- or well-controlled diabetes. The results need to be replicated in additional cohorts before concluding that the clinical assessment of vitamin D status in blacks and whites should follow a single standard. The CaDDM and DDM2 trials were registered at clinicaltrials.gov as NCT00436475 and NCT01736865, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 45 publications
(88 reference statements)
1
58
1
Order By: Relevance
“…However, these results have been questioned owing to technical problems inherent in the VDBP assay used in their studies that led to overestimation of C f and bioavailable concentrations 31–34 . More recent studies have measured C f directly (thereby avoiding issues related to VDBP binding) in patients and reported that C f of vitamin D 3 are generally lower in African Americans depending on physiological or disease state 18,26,35 . For example, directly measured C f were identical in African American and White healthy post menopausal women 18 while in patients with Type 2 Diabetes 35 directly measured C f were lower in African Americans compared to Whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results have been questioned owing to technical problems inherent in the VDBP assay used in their studies that led to overestimation of C f and bioavailable concentrations 31–34 . More recent studies have measured C f directly (thereby avoiding issues related to VDBP binding) in patients and reported that C f of vitamin D 3 are generally lower in African Americans depending on physiological or disease state 18,26,35 . For example, directly measured C f were identical in African American and White healthy post menopausal women 18 while in patients with Type 2 Diabetes 35 directly measured C f were lower in African Americans compared to Whites.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have measured C f directly (thereby avoiding issues related to VDBP binding) in patients and reported that C f of vitamin D 3 are generally lower in African Americans depending on physiological or disease state 18,26,35 . For example, directly measured C f were identical in African American and White healthy post menopausal women 18 while in patients with Type 2 Diabetes 35 directly measured C f were lower in African Americans compared to Whites. The results of our study show that C f of vitamin D 3 in African Americans with moderate asthma on ICS are lower compared to Whites at baseline (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies also find weak but statistically significant inverse relationships between iPTH and free 25(OH)D in normal subjects and prediabetics [39 49 61 65 66]. Areas of uncertainty include relationships between free 25(OH)D and race, birth control pills, pregnancy in the second and third trimester, and biomarkers of vitamin D effects on bone.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…PTH is negatively correlated with free 25(OH)D as well as total 25(OH)D. Serum C-terminal telopeptide of type I collagen has been reported to have a moderate positive correlation with total and free 25(OH)D [67]. With vitamin D supplementation, free 25(OH)D concentrations rise in concert with total 25(OH)D concentrations [[65 67] [64] [68], rising more steeply with D3 supplementation compared to D2 [66]. With high dose D supplementation the changes in iPTH were significantly related to changes in free 25(OH)D but not to changes in total 25(OH)D or changes in total 1,25(OH) 2 D [66].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Many factors such as obesity, smoking, diets high in fat and red meat, alcohol use, and low vitamin D may contribute [912]. We are now understanding that there may be differences in tumor biology between racial groups; Blacks tend to be diagnosed with CRC at a younger age, present with more proximal, advanced, and aggressive tumors, and are more likely to have KRAS mutations [13–18].…”
Section: 1 Introductionmentioning
confidence: 99%